(untitled) (LIS TODAY, 2025)
This study compares Bangladeshi MOOC-based learning institutions to examine the current situation of online learning platforms in Bangladesh. Purposive sampling in survey research was used to collect data from five institutions in Dhaka, including government and commercial organizations. The purpose of the study was to investigate the following topics: the reasons for providing online courses; the kinds of courses and materials offered; the target audience; teaching strategies; learner activities; and the difficulties faced by MOOC providers. A standardized questionnaire with a five-point Likert scale was used to gather the data. Descriptive statistics were employed to analyze the data. The results show various course offerings, emphasizing spoken language instruction, admission and skill development courses, and curriculum support resources for secondary schools. The primary target audience consists of adults and students, with the institutions hoping to lower the cost of education, improve accessibility, and close the gap between formal and informal education. In addition to exams and assignments, the study lists web-based communication platforms, multimedia tools, and video recordings as common instructional techniques. On the other hand, issues with learner motivation, restricted internet connection, real time engagement, and the quality of the course materials were also noted as common challenges. Based on these results, the study suggests introducing interactive elements, improving content accessibility and clarity, developing student engagement, and overcoming communication gaps to customize learning materials to varied learner requirements. This research adds to our understanding of the MOOC-based learning environment that exists in Bangladesh today and offers insightful information for future growth and development that will increase the overall efficacy of this teaching strategy.